Pharmaceuticals and Personal Care Products in Municipal Wastewater and the Marine Receiving Environment Near Victoria Canada - Krogh, Jeremy; Lyons, Shirley; Lowe, Christopher J. (Frontiers in Marine Science, 2017)
Concerns over the fate of pharmaceuticals and personal care products (PPCP) within the environment have been growing with the advent of more precise analytical methods. The discharge of municipal wastewater has been identified as a significant source of these contaminants, particularly where wastewater treatment is minimal. Here we present results from a comprehensive monitoring regime located around Victoria, BC, Canada. Samples were collected between 2009 and 2016 from a variety of sources including marine water, sediment and biota adjacent to two major untreated sewage outfalls, as well as the sewage itself. PPCP concentrations within the untreated sewage were high, and the sediment surrounding the outfalls showed corresponding contamination. However, this contamination dropped quickly with distance from the outfall such that by 800 m distance most PPCPs were below detection limits. Tissue samples of resident Northern Horse mussels (Modiolus modiolus) collected adjacent to one of the major sewage outfalls showed high single sample concentrations of the antimicrobial triclosan (317 ng g-1 dry weight), the antibiotic ciprofloxacin (176 ng g-1 dry weight), as well as the antidepressant sertraline (84.1 ng g-1 dry weight). Reference stations from around the region showed very low concentrations of contamination with almost all PPCP concentrations being below detection limits. Within the sewage, concentrations were largely stable overtime, with the exception of triclosan and triclocarban which both showed declines over the study period.